ELT Materials from J.Bellot to S.Jobs in Kazakhstan - Cig, Enes Kurtay; Yaylaci, Yusuf; Bayimbetov, Berdak (Journal of Oriental Studies, 2016)
since the globalization processes and international businesses push the more convenient communication among the societies and people, the demand for learning international languages has been increasing. surely, this phenomenon is also observed in Kazakhstan since its independence. this article reviews the various approaches of teaching foreign language, from its early history up to present day of modern communication technologies. Mainly, this work discusses the importance of teacher ingenuity and inspiration and qualitative textbooks in general teaching. experimenting among the students, this work proves that creating of new types of textbooks is quiet easy and mentioned features make the language learning a lot more productive and effective.